Problem Caused by Speech Rhythm in EFL University Students' Perception of Natural Speech - ibrahim, alam-ad-deen (Gezira Journal of Educational Sciences and Humanities; مجلد 17 عدد 2 (2020), 2021)
Speech rhythm is one of the most important phonological features that characterize natural speech in English. Other such phonological features include assimilation and prosodic stress. The main objective of this study was to investigate the extent to which speech rhythm caused problems of speech perception to EFL university students. The descriptive analytical method was adopted. The sample for the study comprised (40) students and (10) teachers at the Department of English, Faculty of Education (Hantoub), University of Gezira. The students took a diagnostic listening test, whereas the teachers responded to a questionnaire. The data obtained was analyzed manually through frequency and percentage. The main findings of the study were that speech rhythm is among phonological features which contribute most to students' failure to perceive natural speech, and that effective techniques for solving the problem include listening to audio recordings in the language laboratory and more teacher's use of English during classes. Based on these findings, the study recommends that EFL university departments should allocate courses for listening comprehension which focus on such phonological features as speech rhythm, and that EFL university students should dedicate some of their time to listening to English auditory mass media like radio stations and TV channels.